Report of the Task Force Financing Plan for Airports - Planning Commission (Planning Commission, 2006)
This Report outlines the financing plan for upgrading and augmenting the airport infrastructure in India. It responds to the direction of the Committee on Infrastructure, chaired by the Prime Minister, to evolve a plan for creating world-class airport infrastructure. The Report was prepared by a Task Force chaired by Shri Anwarul Hoda, Member, Planning Commission, and including experts and representatives from the Ministry of Civil Aviation, the Airports Authority of India, Planning Commission and Ministry of Finance. It was considered and approved by the Committee on Infrastructure in June 2006. The quality of airport infrastructure contributes directly to a country’s international competitiveness and economic growth by facilitating the smooth movement of people and high value cargo, spurring trade and tourism.
Planning Commission Government of India
Planning Commission Government of India